A carbon-carbon composite material graphitization degree efficient detection equipment
Patent Information
- Application Number
- CN202611154102.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明提供一种碳碳复合材料石墨化程度高效检测设备,解决了缺乏加热和多角度移动的固定结构在碳碳复合材料石墨化程度检测过程中会影响检测效果和精度的问题
本发明提供一种碳碳复合材料石墨化程度高效检测设备,为了提高碳碳复合材料石墨化程度高效检测效率和精度,通过第一调节组件和第一内螺纹架将活动框安装在固定框的顶部,同时通过第二调节组件和第二内螺纹架将真空吸附框安装在活动框的上方,利用两个驱动组件为第一调节组件和第二调节组件提供旋转驱动力,就可以带动真空吸附框可以前后左右进行多方向调节位置,让样品和检测设备可以快速对齐,提高检测效率,而在真空吸附框的背面开设有一个可以安装带孔加热板的安装口,通过带孔加热板为真空吸附框上的检测样品进行二次加热或者维持在需要的温度,有利于提高碳碳复合材料石墨化程度检测精度,通过设计可以在碳碳复合材料石墨化程度检测时对样品进行快速精准位置调节,同时配合带孔加热板可以为样品加热,有利于提高检测精度和效率。
Smart Images

Figure CN122983012A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphitization detection technology for carbon-carbon composite materials, and in particular to a high-efficiency detection device for the degree of graphitization of carbon-carbon composite materials. Background Technology
[0002] Carbon-based composite materials are ultra-high temperature composite materials with carbon fiber fabrics or silicon carbide ceramic fiber fabrics as reinforcement and carbon as the matrix. They possess properties such as lightweight, high strength, high temperature resistance, and corrosion resistance. Carbon-carbon composite materials are composite materials with carbon fiber reinforcement and carbon as the matrix, and their advantages include high temperature resistance, high strength, low density, thermal shock resistance, and corrosion resistance. The most important performance characteristic is that the strength does not decrease at high temperatures.
[0003] The degree of graphitization in carbon-carbon composites is primarily determined using X-ray diffraction and Raman spectroscopy. X-ray diffraction calculates the degree of graphitization by measuring the interlayer spacing of graphite crystals, while Raman spectroscopy assesses the degree of graphitization by analyzing characteristic peaks in the spectrum.12 The detection methods are: X-ray diffraction: measuring the interlayer spacing d002 of graphite crystals and substituting it into the Mering-Maire formula to calculate the degree of graphitization; this method can quantitatively assess the degree of graphitization in carbon materials.13 Raman spectroscopy: assessing the degree of graphitization by analyzing characteristic peaks in the spectrum, such as the intensity ratio of the D peak and the G peak. Raman spectroscopy can provide information about the structural order of carbon materials.
[0004] In the process of efficient detection of graphitization degree of carbon-carbon composite materials, it is generally necessary to fix and clamp the sample, and there are certain requirements for temperature. However, the existing fixing and clamping structure lacks multi-angle adjustment structure and heating structure, which will affect the efficiency and accuracy of monitoring the graphitization degree of carbon-carbon composite materials.
[0005] Therefore, it is necessary to provide an efficient detection device for the graphitization degree of carbon-carbon composite materials to solve the above-mentioned technical problems. Summary of the Invention
[0006] This invention provides a high-efficiency detection device for the graphitization degree of carbon-carbon composite materials, which solves the problem that the lack of a fixed structure with heating and multi-angle movement affects the detection effect and accuracy in the process of detecting the graphitization degree of carbon-carbon composite materials.
[0007] To solve the above-mentioned technical problems, the present invention provides a high-efficiency detection device for the graphitization degree of carbon-carbon composite materials, comprising: a base plate; A testing platform is fixedly connected to the top of a base plate. A fixed frame is installed on the top of the testing platform. A first adjusting component is installed inside the fixed frame. The first adjusting component includes an adjusting screw and a sliding rod. A first internal threaded bracket is installed on the outer surface of the first adjusting component. A movable frame is installed on the top of the first internal threaded bracket. A second adjusting component is installed inside the movable frame. A second internal threaded bracket is installed on the outer surface of the second adjusting component. A vacuum adsorption frame is installed on the top of the second internal threaded bracket via four support bolts. A frame is installed on the top of the vacuum adsorption frame. An installation port is opened on the back of the vacuum adsorption frame. A perforated heating plate is installed inside the installation port. A connecting wire is installed on the back of the perforated heating plate. A driving component is installed on one side of both the fixed frame and the movable frame. Two exhaust hoods are installed at the bottom of the vacuum adsorption frame. A connecting pipe with a valve is installed on the back of each of the two exhaust hoods. The other end of each of the two valves is connected to the outer surface of the collection pipe. The mounting bracket is installed on top of the testing table. A lifting assembly is mounted on the top of the mounting bracket. The telescopic end of the lifting assembly is connected to a fixed base via a quick-release assembly. The testing equipment is mounted on the bottom of the fixed base. A filter assembly and an exhaust assembly are mounted on the back of the testing table. An exhaust pipe is installed on one side of the filter assembly. The adjusting screw and the fixed frame are rotatably connected, the slide rod and the first internal threaded frame are slidably connected, the adjusting screw and the first internal threaded frame are threadedly connected, the holes on the perforated heating plate facilitate air circulation, the vacuum adsorption frame is made of a fast heat-conducting material, one of the drive components is installed on the back of the movable frame, and the other drive component is installed on one side of the fixed frame. The drive component provides rotational driving force for the first adjusting component and the second adjusting component.
[0008] Preferably, a control box with a door is installed on the top of the base plate, and a control switch is installed on the front of the testing platform; Control switches can control the operation of equipment.
[0009] Preferably, an auxiliary positioning device is mounted on the front of the fixed base via a fixing frame, and the lifting assembly includes a telescopic component and a stabilizing rod; The auxiliary positioning device can help to accurately position the sample and testing equipment. One end of the telescopic component and the stabilizer bar are connected to the top of the quick-release assembly.
[0010] Preferably, the quick-release assembly includes an installation structure, a docking structure, and a fixing structure, wherein the fixing structure is used to install the docking structure inside the installation structure; The two sides of the docking structure have holes for threaded connection with the fixing structure.
[0011] Preferably, the drive assembly includes a protective shell, a drive component, and an angle sensor. The angle sensor, in conjunction with the drive component controller, is used to precisely control the rotation speed and rotation angle. The filter assembly includes a filter box and an interception component. The filter box is used to install the dust interception component. The top of the filter box is equipped with a cover.
[0012] Preferably, the exhaust assembly includes a mounting housing, an exhaust component, a connecting pipe, and a discharge pipe, wherein the connecting pipe is used to connect the inlet of the exhaust component and the filter box.
[0013] Preferably, mounting slots are provided on both sides of the fixed base, and a back light shield is installed on the back of the fixed base; The back light shield is fixed to the back of the fixed base by brackets and bolts. The front of the back light shield has an opening at the top position for inserting the card strip.
[0014] Preferably, side light-shielding plates are installed on both sides of the fixed base via a docking assembly. The docking assembly includes a docking frame and a locking strip. The docking frame is used to fix the locking strip to the top of the side light-shielding plate.
[0015] Preferably, a front light-shielding plate is installed on the front of the fixed base, and two magnetic components are installed on both sides of the front light-shielding plate. The magnetic assembly is used to mount the front sunshade to the front of the fixed base.
[0016] Preferably, the magnetic suction assembly includes a magnetic block and an iron block, the magnetic block being connected to both sides of the front light-blocking plate, and the iron block being connected to both sides of the side light-blocking plate.
[0017] Compared with related technologies, the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by this invention has the following advantages: This invention provides a high-efficiency detection device for the graphitization degree of carbon-carbon composite materials. To improve the efficiency and accuracy of the detection, a movable frame is mounted on top of a fixed frame via a first adjusting component and a first internal threaded bracket. Simultaneously, a vacuum adsorption frame is mounted above the movable frame via a second adjusting component and a second internal threaded bracket. Two driving components provide rotational driving force to the first and second adjusting components, allowing the vacuum adsorption frame to be adjusted in multiple directions (front, back, left, and right), enabling rapid alignment of the sample and the detection device and improving detection efficiency. A perforated heating plate is installed on the back of the vacuum adsorption frame, allowing for secondary heating of the sample or maintenance at the required temperature, which further improves the accuracy of the carbon-carbon composite material graphitization degree detection. This design enables rapid and precise position adjustment of the sample during carbon-carbon composite material graphitization degree detection, and the perforated heating plate further enhances detection accuracy and efficiency. Attached Figure Description
[0018] Figure 1 A schematic diagram of the structure of the first embodiment of the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by the present invention; Figure 2 A schematic diagram of the exhaust assembly is provided for this invention; Figure 3 A schematic diagram of the structure of the vacuum adsorption frame is provided for this invention; Figure 4 Provided for the present invention Figure 1 An enlarged view of point A shown; Figure 5 Provided for the present invention Figure 3 An enlarged view of point B shown; Figure 6 A schematic diagram of the drive component is provided for this invention; Figure 7 A schematic diagram of the structure of the second embodiment of the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by the present invention; Figure 8 A schematic diagram of the side light-shielding plate is provided for this invention; Figure 9 Provided for the present invention Figure 8 A magnified view of point C shown.
[0019] Numbered components in the diagram: 1. Base plate; 2. Control box; 3. Box door; 4. Testing platform; 5. First adjustment assembly; 501. Adjusting screw; 502. Slide rod; 6. Drive assembly; 601. Protective shell; 602. Drive component; 603. Angle sensor; 7. Fixed frame; 8. Movable frame; 9. Mounting bracket; 10. Testing equipment; 11. Lifting assembly; 111. Telescopic component; 112. Stabilizing bar; 12. Quick-release assembly; 121. Mounting structure; 122. Docking structure; 123. Fixed structure; 13. Fixed base; 14. Mounting slot; 15. Fixed bracket; 16. Auxiliary positioning device; 17. Second adjustment assembly; 18. Control switch; 19. Exhaust pipe; 2 0. Filter assembly; 201. Filter box; 202. Interception component; 21. Exhaust assembly; 211. Mounting shell; 212. Exhaust component; 213. Connecting pipe; 214. Discharge pipe; 22. First internal threaded bracket; 23. Vacuum adsorption frame; 24. Perforated heating plate; 25. Mounting port; 26. Frame; 27. Exhaust hood; 28. Connecting pipe; 29. Valve; 30. Collection pipe; 31. Connecting wire; 32. Second internal threaded bracket; 33. Support bolt; 34. Rear light shield; 35. Side light shield; 36. Magnetic assembly; 361. Magnetic block; 362. Iron block; 37. Front light shield; 38. Docking assembly; 381. Docking frame; 382. Locking strip. Detailed Implementation
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0021] Please refer to the following: Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 ,in, Figure 1 A schematic diagram of the structure of the first embodiment of the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by the present invention; Figure 2 A schematic diagram of the exhaust assembly is provided for this invention; Figure 3 A schematic diagram of the structure of the vacuum adsorption frame is provided for this invention; Figure 4 Provided for the present invention Figure 1 An enlarged view of point A shown; Figure 5 Provided for the present invention Figure 3 An enlarged view of point B shown; Figure 6 A schematic diagram of the driving component is provided for this invention. The high-efficiency detection device for the graphitization degree of carbon-carbon composite materials includes: a base plate 1; A testing platform 4 is fixedly connected to the top of the base plate 1. A fixed frame 7 is installed on the top of the testing platform 4. A first adjusting component 5 is installed inside the fixed frame 7. The first adjusting component 5 includes an adjusting screw 501 and a sliding rod 502. A first internal threaded bracket 22 is installed on the outer surface of the first adjusting component 5. A movable frame 8 is installed on the top of the first internal threaded bracket 22. A second adjusting component 17 is installed inside the movable frame 8. A second internal threaded bracket 32 is installed on the outer surface of the second adjusting component 17. The top of the second internal threaded bracket 32 is supported by four support bolts 3. 3. A vacuum adsorption frame 23 is installed. A frame 26 is installed on the top of the vacuum adsorption frame 23. An installation port 25 is opened on the back of the vacuum adsorption frame 23. A perforated heating plate 24 is installed inside the installation port 25. A connecting line 31 is installed on the back of the perforated heating plate 24. A drive assembly 6 is installed on one side of both the fixed frame 7 and the movable frame 8. Two exhaust hoods 27 are installed at the bottom of the vacuum adsorption frame 23. A connecting pipe 28 with a valve 29 is installed on the back of each of the two exhaust hoods 27. The other end of each of the two valves 29 is connected to the outer surface of the collection pipe 30. Mounting bracket 9 is installed on top of testing table 4. A lifting assembly 11 is mounted on the top of mounting bracket 9. A fixed base 13 is mounted to the telescopic end of the lifting assembly 11 via a quick-release assembly 12. Testing equipment 10 is mounted on the bottom of the fixed base 13. A filter assembly 20 and an exhaust assembly 21 are respectively mounted on the back of testing table 4. An exhaust pipe 19 is mounted on one side of the filter assembly 20. The adjusting screw 501 is rotatably connected to the fixed frame 7, the slide rod 502 is slidably connected to the first internal threaded frame 22, and the adjusting screw 501 and the first internal threaded frame 22 are threadedly connected. The holes on the perforated heating plate 24 facilitate air circulation. The vacuum adsorption frame 23 is made of a fast heat-conducting material. One drive component 6 is installed on the back of the movable frame 8, and the other drive component 6 is installed on one side of the fixed frame 7. The drive component 6 provides rotational driving force for the first adjusting component 5 and the second adjusting component 17. The connecting line 31 is connected to the temperature control device to control the temperature of the perforated heating plate 24. The detection device 10 integrates a Raman spectrometer, an infrared spectrometer, and a thermogravimetric analyzer. The other end of the exhaust pipe 19 is connected to the collection pipe 30.
[0022] A control box 2 with a door 3 is installed on the top of the base plate 1, and a control switch 18 is installed on the front of the detection table 4; The control switch 18 can control the operation of the equipment. The control box 2 is equipped with a power switch and a controller for controlling the operation of the equipment. The box door 3 is equipped with a lock.
[0023] The front of the fixed base 13 is equipped with an auxiliary positioning device 16 via a fixing frame 15. The lifting assembly 11 includes a telescopic component 111 and a stabilizing rod 112. The auxiliary positioning device 16 can assist the sample and the testing device 10 in accurate positioning. One end of the telescopic component 111 and the stabilizer 112 is connected to the top of the quick-release assembly 12. The stabilizer 112 passes through the mounting frame 9, which can increase the stability of the quick-release assembly 12.
[0024] The quick-release assembly 12 includes a mounting structure 121, a docking structure 122, and a fixing structure 123, wherein the fixing structure 123 is used to install the docking structure 122 inside the mounting structure 121. The mounting structure 121 has openings on the front and bottom, and the mating structure 122 has holes on both sides for threaded connection with the fixing structure 123.
[0025] The drive assembly 6 includes a protective shell 601, a drive component 602, and an angle sensor 603. The angle sensor 603 works with the drive component 602 controller to precisely control the rotation speed and rotation angle. The filter assembly 20 includes a filter box 201 and an interception component 202. The filter box 201 is used to install the dust interception component 202. The top of the filter box 201 is equipped with a cover.
[0026] The exhaust assembly 21 includes a mounting housing 211, an exhaust component 212, a connecting pipe 213, and an outlet pipe 214. The connecting pipe 213 is used to connect the inlet of the exhaust component 212 to the filter box 201. The exhaust component 212 is used to provide suction.
[0027] The working principle of the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by this invention is as follows: The movable frame 8 is mounted on top of the fixed frame 7 via the first adjusting component 5 and the first internal threaded bracket 22. Simultaneously, the vacuum adsorption frame 23 is mounted above the movable frame 8 via the second adjusting component 17 and the second internal threaded bracket 32. Two driving components 6 provide rotational driving force to the first adjusting component 5 and the second adjusting component 17, allowing the vacuum adsorption frame 23 to be adjusted in multiple directions (front, back, left, and right) to quickly align the sample and the detection device 10, improving detection efficiency. A mounting port 25 for a perforated heating plate 24 is provided on the back of the vacuum adsorption frame 23. The perforated heating plate 24 provides secondary heating or maintains the temperature of the sample on the vacuum adsorption frame 23. The required temperature is beneficial to improving the accuracy of the graphitization degree detection of carbon-carbon composite materials. In actual use, the carbon-carbon composite material sample to be tested and heated to the corresponding temperature is first placed on the top of the vacuum adsorption frame 23 through the detection plate. Then, the exhaust component 21 is activated to provide suction. With the help of the two exhaust hoods 27, a negative pressure can be formed between the vacuum adsorption frame 23 and the sample, adsorbing the sample above the vacuum adsorption frame 23. Then, the two drive components 6 are activated to drive the sample to perform multi-directional adjustment on the top of the detection stage 4 through the first adjustment component 5 and the second adjustment component 17, so that the sample can be accurately aligned with the detection device 10. Then, the graphitization degree of carbon-carbon composite materials can be detected by the detection device 10.
[0028] Compared with related technologies, the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by this invention has the following advantages: To improve the efficiency and accuracy of graphitization degree detection in carbon-carbon composite materials, a movable frame 8 is mounted on top of a fixed frame 7 via a first adjusting component 5 and a first internal threaded bracket 22. Simultaneously, a vacuum adsorption frame 23 is mounted above the movable frame 8 via a second adjusting component 17 and a second internal threaded bracket 32. Two driving components 6 provide rotational driving force to the first adjusting component 5 and the second adjusting component 17, allowing the vacuum adsorption frame 23 to be adjusted in multiple directions (front, back, left, and right) to quickly align the sample and the detection device 10, improving detection efficiency. A mounting port 25 for a perforated heating plate 24 is provided on the back of the vacuum adsorption frame 23. The perforated heating plate 24 provides secondary heating to the sample on the vacuum adsorption frame 23 or maintains it at the required temperature, which helps improve the accuracy of graphitization degree detection in carbon-carbon composite materials. This design allows for rapid and precise position adjustment of the sample during graphitization degree detection, and the perforated heating plate 24 further enhances detection accuracy and efficiency.
[0029] Second Embodiment Please refer to the following: Figures 7-8 - Figure 9 , Figure 7A schematic diagram of the structure of the second embodiment of the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by the present invention; Figure 8 A schematic diagram of the side light-shielding plate is provided for this invention; Figure 9 Provided for the present invention Figure 8 The enlarged view at point C is shown. Based on the efficient detection device for the graphitization degree of carbon-carbon composite materials provided in the first embodiment of this application, the second embodiment of this application proposes another efficient detection device for the graphitization degree of carbon-carbon composite materials. The second embodiment is merely a preferred embodiment of the first embodiment, and the implementation of the second embodiment will not affect the separate implementation of the first embodiment.
[0030] Specifically, the difference between the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided in the second embodiment of this application is that mounting grooves 14 are provided on both sides of the fixed base 13, and a back light shield 34 is installed on the back of the fixed base 13. The back light shield 34 is fixed to the back of the fixed base 13 by a bracket and bolts. The front of the back light shield 34 has an opening at the top position where the clip 382 can be inserted.
[0031] Both sides of the fixed base 13 are equipped with side light shields 35 via docking components 38. The docking components 38 include docking frames 381 and locking strips 382. The docking frames 381 are used to fix the locking strips 382 to the top of the side light shields 35. The insertion of the 382 clip into the mounting slot 14 increases connection stability.
[0032] The front of the fixed base 13 is equipped with a front light shield 37, and two magnetic components 36 are installed on both sides of the front light shield 37. The magnetic assembly 36 is used to mount the front light shield 37 on the front of the fixed base 13.
[0033] The magnetic suction assembly 36 includes a magnetic block 361 and an iron block 362. The magnetic block 361 is connected to both sides of the front light shield 37, and the iron block 362 is connected to both sides of the side light shield 35. The magnetic block 361 and the iron block 362 attract each other, which can fix the front light shield 37 in place.
[0034] Compared with related technologies, the high-efficiency detection device for the graphitization degree of carbon-carbon composite materials provided by this invention has the following advantages: To reduce the impact of light on the detection of graphitization degree of carbon-carbon composite materials, a mounting groove 14 is opened on both sides of the fixed base 13. At the same time, the back light shield 34 is installed on the back of the fixed base 13, and the two side light shields 35 are installed on both sides of the fixed base 13 through two docking components 38. The locking strips 382 in the docking components 38 are inserted into the inside of the mounting groove 14. After the sample is placed during the test, the front light shield 37 is installed on the front of the two side light shields 35 through two sets of magnetic suction components 36, so that a light-shielding area is formed under the fixed base 13. Then, with the help of the lifting component 11, the vacuum adsorption frame 23 is covered by a light shield, so that the detection device 10 can be detected in a darker environment. This design can reduce the impact of light on the detection device 10 and help improve the detection accuracy.
[0035] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A high-efficiency detection device for the graphitization degree of carbon-carbon composite materials, characterized in that, include: Base plate; A testing platform is fixedly connected to the top of a base plate. A fixed frame is installed on the top of the testing platform. A first adjusting component is installed inside the fixed frame. The first adjusting component includes an adjusting screw and a sliding rod. A first internal threaded bracket is installed on the outer surface of the first adjusting component. A movable frame is installed on the top of the first internal threaded bracket. A second adjusting component is installed inside the movable frame. A second internal threaded bracket is installed on the outer surface of the second adjusting component. A vacuum adsorption frame is installed on the top of the second internal threaded bracket via four support bolts. A frame is installed on the top of the vacuum adsorption frame. An installation port is opened on the back of the vacuum adsorption frame. A perforated heating plate is installed inside the installation port. A connecting wire is installed on the back of the perforated heating plate. A driving component is installed on one side of both the fixed frame and the movable frame. Two exhaust hoods are installed at the bottom of the vacuum adsorption frame. A connecting pipe with a valve is installed on the back of each of the two exhaust hoods. The other end of each of the two valves is connected to the outer surface of the collection pipe. The mounting frame is installed on the top of the testing table. A lifting assembly is installed on the top of the mounting frame. A fixed base is installed on the telescopic end of the lifting assembly via a quick-release assembly. The testing equipment is installed on the bottom of the fixed base. A filter assembly and an exhaust assembly are installed on the back of the testing table. An exhaust pipe is installed on one side of the filter assembly.
2. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, A control box with a door is installed on the top of the base plate, and a control switch is installed on the front of the testing platform.
3. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, An auxiliary positioning device is mounted on the front of the fixed base via a fixing frame, and the lifting assembly includes a telescopic component and a stabilizing rod.
4. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, The quick-release assembly includes an installation structure, a docking structure, and a fixing structure, wherein the fixing structure is used to install the docking structure inside the installation structure.
5. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, The drive assembly includes a protective shell, a drive component, and an angle sensor. The angle sensor, in conjunction with the drive component controller, is used to precisely control the rotation speed and rotation angle. The filter assembly includes a filter box and an interception component. The filter box is used to install the dust interception component.
6. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, The exhaust assembly includes a mounting housing, an exhaust component, a connecting pipe, and an outlet pipe. The connecting pipe is used to connect the inlet of the exhaust component to the filter box.
7. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, The fixed base has mounting slots on both sides, and a back light shield is installed on the back of the fixed base.
8. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, Both sides of the fixed base are equipped with side light shields via docking components. The docking components include docking frames and locking strips. The docking frames are used to fix the locking strips to the top of the side light shields.
9. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 1, characterized in that, The front of the fixed base is equipped with a front light-shielding plate, and two magnetic components are installed on both sides of the front light-shielding plate.
10. The high-efficiency detection equipment for the graphitization degree of carbon-carbon composite materials according to claim 9, characterized in that, The magnetic assembly includes a magnetic block and an iron block. The magnetic block is connected to both sides of the front light-blocking plate, and the iron block is connected to both sides of the side light-blocking plate.